Understanding alcohol-related indicators from population surveys: answering the "Five W's of Epidemiology" - Raquel Brandini De Boni (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
The harmful use of alcohol is a major risk factor for the global burden of disease, and public policies are the most effective strategies to prevent it. Population-based surveys are milestones for planning, implementing, and monitoring those policies. However, there are numerous ways to measure alcohol consumption which may result in different indicators. Researchers and stakeholders should find common ground in the understanding of these measures to avoid misinterpretation and confusion in the field. Answering to the "Five W's Epidemiology", when interpreting alcohol-related information, may improve the communication, as well as reproducibility and comparability of research findings. This paper aims to exemplify this approach by describing some indicators from the World Health Organization's Global Information System on Alcohol and Health (GISAH) and the corresponding data available from the latest Brazilian household surveys. Notably, none of the Brazilian surveys reports on all the nine selected GISAH indicators, and only two provided the necessary methodological details to be fully reproducible. A stronger agenda is of the utmost importancefor advancing in the monitoring and prevention of alcohol-related harms in Brazil.